Addison's disease and pregnancy. Presentation of a case and review of the literature (1974)
The first case of Addison's disease during pregnancy is published in the Colombian literature with suggested treatment of 0.1 mg of Fluorcortisone and minimal dosages of Prednisone to maintain the patient asymptomatic but avoid over dosage of medicine. Birth is awaited through natural means, preapplying medicines to the patient with a charge of 200 mg. of hydrocortisone per day two days prior to fixing the date of an induction of a term birth. The newborn was observed with regard to data on hyperpotassemia, hyponatremia and hypoglycemia. (Journal received: 19 Sept. 1975)